THE EFFECT OF PRESSURE ON ARAGONITE DISSOLUTION RATES IN SEAWATER - Gacker J.; Hbyrne R.; Rbetzer P.; Ben-Yaakov S.; Afeely R. (My University, 1987)
Aragonite dissolution in sea water at variable pressure is well described by the equation Rate = kappa'((COâ/sup 2 -/)s - (COâ/sup 2 -/))/sup n/ where (COâ/sup 2 -/)s is the carbonate ion concentration at saturation, (COâ/sup 2 -/) is the observed carbonate ion concentration, and kappa' and n are empirical constants. Application of the equation Rate = kappa(1-Omega)/sup n/ to descriptions of aragonite dissolution rates is appropriate at constant pressure, temperature and salinity. The authors measurements in sea water at 5Â°C are consistent with the estimate - ..delta.. V = 36.5 cmÂ³mole for the volume change accompanying aragonite dissolution. This result is somewhat higher than laboratory estimates, but lower than estimates based on calcite and the difference between calcite and aragonite molar volumes.